Cubic Copper Hexacyanoferrates Nanoparticles: Facile Template-Free Deposition and Electrocatalytic Sensing Towards Hydrazine - Xingxing Wang; Yun Zhang; Shan Jiang; Xiaobo Ji; Yong Liu; Craig E. Banks (International Journal of Electrochemistry)
Cubic copper hexacyanoferrate (CuHCF) nanoparticles prepared via electrolytic deposition are presented with their morphology and crystalline structure characterized with SEM and XRD. The advantage of this methodology is that it allows the fabrication of uniform cubic nanoparticles with permeable structures onto the desired underlying electrode substrate. It was observed that the CuHCF film acts as a permeable membrane for cations such as K+, Na+, Li+, and NH4+ with a selection order of K+> Li+>NH4+> Na+. Furthermore, the analytical utility of these cubic-like CuHCF morphologies supported on a glassy carbon electrode was evaluated towards the electrochemical oxidation of hydrazine which was found to exhibit a linear response over the range 66 𝜇M to 17 mM with a detection limit corresponding to 16.5 𝜇M.